(untitled) (Journal of NELTA, 2010)
The implementation of teaching practice in ELT is an effective way in improving practices of our student teachers. This study therefore focuses on assessment of teaching practice conducted by the School of Education, Kathmandu University for M.Ed ELT student teachers. A total of 16 student teachers, 100 students, 16 co- teachers and 16 principals of higher educational institutions involved in the study. The study reveals that there has been an improvement in teaching practice particularly on classroom dynamics. However enough training on lesson plan preparation, presentation, class management, communication skills, evaluation and project work is necessary to our student teachers in order to improve English language teaching. The study is expected to be useful to academic planners, ELT planners, curriculum designers, textbook writers, teachers and practitioners. Key words: Teaching practice, reflection, student-teachers, lesson plan DOI: 10.3126/nelta.v14i1.3102 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 138-145